2021
DOI: 10.1371/journal.pcbi.1008688
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the feasibility and effectiveness of household-pooled universal testing to control COVID-19 epidemics

Abstract: Outbreaks of SARS-CoV-2 are threatening the health care systems of several countries around the world. The initial control of SARS-CoV-2 epidemics relied on non-pharmaceutical interventions, such as social distancing, teleworking, mouth masks and contact tracing. However, as pre-symptomatic transmission remains an important driver of the epidemic, contact tracing efforts struggle to fully control SARS-CoV-2 epidemics. Therefore, in this work, we investigate to what extent the use of universal testing, i.e., an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 44 publications
(65 reference statements)
0
29
0
Order By: Relevance
“…Households or groups of several households have been encouraged to limit their contact with others during the pandemic to reduce the number of close contacts of any individual and hence the risk of transmission. A study that simulated pooling of households and the social interactions between them concluded that the whole Belgian population of 11 million individuals could be tested within 4 weeks, 38 similar to the achievement of Chinese health authorities in screening the 11 million residents of Wuhan province in 2 weeks in 2020. 4 …”
Section: Strategiesmentioning
confidence: 85%
“…Households or groups of several households have been encouraged to limit their contact with others during the pandemic to reduce the number of close contacts of any individual and hence the risk of transmission. A study that simulated pooling of households and the social interactions between them concluded that the whole Belgian population of 11 million individuals could be tested within 4 weeks, 38 similar to the achievement of Chinese health authorities in screening the 11 million residents of Wuhan province in 2 weeks in 2020. 4 …”
Section: Strategiesmentioning
confidence: 85%
“…A recent review of scaling testing highlighted the role of population screening in combating the COVID-19 pandemic 1 . Compared to the Dorfman pooling, more sophisticated testing algorithms that may be more efficient have been proposed in the literature, including hypercube pooling testing 7 , non-random pool allocations 8 , multi-stage hierarchical pool testing 9 , and combinatorial non-hierarchical pool testing 10 , 11 . However, such sophisticated testing algorithms can be difficult to implement, especially in population screening.…”
Section: Introductionmentioning
confidence: 99%
“…Although the literature on Dorfman pooling and antigen testing has grown rapidly, the cost-effectiveness of different testing technologies and strategies under fast-changing epidemic dynamics remains unclear. Within the framework of simple Dorfman pooling, most recent studies have focused on the optimal design of pool size, modifications of the pooling workflows, and corresponding laboratory validation 7 , 8 , 10 , 12 16 . The efficiency, accuracy 7 , 12 , 14 , and cost-effectiveness 17 of pooled testing were evaluated under a set of static points of prevalence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations